Langmuir-Schaefer Film Investigation and Density Functional Theory Band Gap Calculations of Calix[n]arene-Para-Aminobenzoic Acid for Drug Nanosensor Application - Faridah Lisa binti Supian, Afiq bin Radzwan, Mazlina binti Musa (Tanjung Malim, 2024)
Langmuir-Schaefer Film Investigation and Density Functional Theory Band Gap Calculations of Calix[n]arene-Para-Aminobenzoic Acid for Drug Nanosensor Application by Faridah Lisa binti Supian, Afiq bin Radzwan, Mazlina binti Musa